2010
DOI: 10.1152/ajpheart.00699.2009
|View full text |Cite
|
Sign up to set email alerts
|

Glucose enhances expression of TRPC1 and calcium entry in endothelial cells

Abstract: Hyperglycemia is a major risk factor for endothelial dysfunction and vascular disease, and in the current study, the link to glucose-induced abnormal intracellular Ca2+ (Cai2+) homeostasis was explored in bovine aortic endothelial cells in high glucose (HG; 25 mmol/l) versus low glucose (LG; 5.5 mmol/l; control). Transient receptor potential 1 (TRPC1) ion channel protein, but not TRPC3, TRPC4, or TRPC6 expression, was significantly increased in HG versus LG at 72 h. HG for 4, 24, and 72 h did not change basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 61 publications
4
27
0
1
Order By: Relevance
“…TRPC1 is engaged by a number of inflammatory agonists, such as ATP, thrombin, tumor necrosis factor (ΤΝF)-α, and angiotensin II (AngII), and by growth factors, such as VEGF and bFGF [5,12,148,[207][208][209] . TRPC1 may act as a SOC due to its ability to interact with InsP3Rs through several signaling cascades.…”
Section: Trpc Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPC1 is engaged by a number of inflammatory agonists, such as ATP, thrombin, tumor necrosis factor (ΤΝF)-α, and angiotensin II (AngII), and by growth factors, such as VEGF and bFGF [5,12,148,[207][208][209] . TRPC1 may act as a SOC due to its ability to interact with InsP3Rs through several signaling cascades.…”
Section: Trpc Channelsmentioning
confidence: 99%
“…Finally, TRPC1 may be involved in endothelial tube formation both in vitro [224] and in vivo [225] . The expression of TRPC1 in vascular ECs may be increased by high glucose levels, with a consequent increase in the amplitude of agonistinduced Ca 2+ influx and a dramatic impact on endothelial function in diabetic patients [209] . TRPC1 not only acts as an SOC in vascular endothelium, but may also serve as an MSC by assembling with TRPV4 to mediate flow-induced Ca 2+ entry in vascular endothelium [226] .…”
Section: +(Wb Ihc) +(Wb Ihc) +(Wb Ihc)mentioning
confidence: 99%
“…Hyperglycemia is a pathological hallmark of diabetic complications, such as diabetic retinopathy (DR), and hyperglycemia can also increase the intracellular free calcium concentration ([Ca 2+ ] i ) in various cell types [1][2][3][4] . An increase in [Ca 2+ ] i has been shown to play an important role in the pathogenesis of angiogenesis [5,6] , which is the most common cause of blindness in DR. Vascular endothelial growth factor (VEGF) is one of the most potent angiogenic factors produced by retinal ischemia [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in bovine aortic endothelial cells, Bishara and Ding showed that high glucose treatment at 25 mM for 24 and 72 h resulted in a sustained increase in SOCE following activation of the P 2 Y receptor by ATP. 113 They proposed that the TRPC1 protein contributed to the enhanced SOCE because TRPC1 protein expression was elevated after 72-h high glucose treatment, and antisense TRPC1 treatment attenuated the ATP-induced Ca 2þ response. However, it is not clear whether the TRPC1 protein functions as an SOC itself or as a regulator/modulator of SOC in that study.…”
Section: Soce and Diabetic Vasculopathymentioning
confidence: 99%